Significance of post-game-specificity skills coaching on rhythmic coupling coordination case players handball positions - Mohammed, Z. (The Russian Journal of Physical Education and Sport, 2017)
Thus, all sports require the coordination of eyes, hands and/or feet as crucial for tactical athletes. Our question based on the injury of post-game training in the development of this quality mortice. Deduced by the researcher, in the case of limbs mainly involves movements, which require the sequential and simultaneous of the both body sides, using the sensor-motor ability to organise the temporal motor responses1. Where the differences between individuals are defined in reaction time, time of motion2, intelligence 3, and cognitive control as essential and decisive factors of superiority in individual dual-task coordination4. While in the case of collective skill the differences are related to the teams spatiotemporal behaviour, according to the similar studies5.Materials.Through the above, our aims of this current study are to examine the consequence of Post-Game-Specific skills experiences training on income and efficiency in dual-task coordination as their relationships with interlimb coordination rhythmic case rotation as a protocol integrated into the current experience. Research methods:To achieve this goal, 36 players under17 years, from different clubs handball Sidi bel abbes were selected by the intentional method, according to their post-game experience (pivots (12)- backcourts (12) -wings (12)) for the years 2015-2016 and their achievements rate eye-hand coordination skills in the initial test.Results. Based on the proposed protocol and applied statistical analysis (P = 0.05). We confirm that assessment of rhythmic coupling coordination requires the integration of the rotation to analyses the defect in individual dual-task coordination. Confirmed in the present study, in the differences recorded in favour of the pivots followed by the backcourts at least for the wing players, due to the conventional training methods and tactical combinations according to similar studies.Condition.Founded on these differences acquired by the research team. We emphasise our coaches and players to develop the Interlimb coordination rhythmic. Founded not only on technical post-game requirements, but also the changes in role positions in the case of wings at least exposed to this skill 6.